2013
DOI: 10.1371/journal.pone.0054444
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Mapping and Characteristics of Genes Specifically or Preferentially Expressed during Fiber Development in Cotton

Abstract: Cotton fiber is an ideal model to study cell elongation and cell wall construction in plants. During fiber development, some genes and proteins have been reported to be specifically or preferentially expressed. Mapping of them will reveal the genomic distribution of these genes, and will facilitate selection in cotton breeding. Based on previous reports, we designed 331 gene primers and 164 protein primers, and used single-strand conformation polymorphism (SSCP) to map and integrate them into our interspecific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 40 publications
1
13
0
Order By: Relevance
“…This hypothesis based on the expression data strongly agrees with the empirical data reported [41]. Similar results were reported [42], who performed RT-PCR analysis of the QTL primers that are preferentially expressed between G. hirsutum Emian22 and G. barbadense 3-79 during fiber development. Expression of FPG012 primer, tightly linked with a QTL marker, reached a peak at 20 DPA in Emian 22, while the expression peak appeared at 25 DPA in 3-79.…”
Section: Protein Ubiquitination and Fiber Developmentsupporting
confidence: 91%
See 1 more Smart Citation
“…This hypothesis based on the expression data strongly agrees with the empirical data reported [41]. Similar results were reported [42], who performed RT-PCR analysis of the QTL primers that are preferentially expressed between G. hirsutum Emian22 and G. barbadense 3-79 during fiber development. Expression of FPG012 primer, tightly linked with a QTL marker, reached a peak at 20 DPA in Emian 22, while the expression peak appeared at 25 DPA in 3-79.…”
Section: Protein Ubiquitination and Fiber Developmentsupporting
confidence: 91%
“…Expression of FPG012 primer, tightly linked with a QTL marker, reached a peak at 20 DPA in Emian 22, while the expression peak appeared at 25 DPA in 3-79. Based on the expression data between the two lines, it was suggested that the delay in gene expression may be responsible for the higher fiber strength of 3-79 than Emian 22 [42]. It is possible that the expression peak of GhRING2 in CS-B25 fiber is not at 20 DPA, but at the late secondary wall synthesis stage.…”
Section: Protein Ubiquitination and Fiber Developmentmentioning
confidence: 99%
“…To date, several thousands of SSR and SNP markers have been developed in cotton (Blenda et al 2012;Fang and Yu 2012;Guo et al 2007;Lacape et al 2009;Yu et al 2012a) and they have been surveyed for polymorphism against a 12-genotype germplasm standard (diversity panel) of six Gossypium species ). The localization of SSR and SNP markers to all 26 chromosomes and the creation of highdensity genetic maps for the tetraploid cotton genome provide opportunities to identify genetic factors controlling and regulating the expression of traits of interest (Lacape et al 2013;Li et al 2013;Marathi et al 2012;Zhu et al 2011). However, due to the allopolyploid nature of the cotton genome, certain chromosomal structures remain to be resolved.…”
Section: Introductionmentioning
confidence: 99%
“…Many cotton QTL mapping studies were conducted using either F 2 or BC 1 populations Draye et al 2005;Jiang et al 1998;Kohel et al 2001;Lacape et al 2005;Li et al 2013;Shen et al 2005). These QTL studies also employed either single marker regression without a genetic map or interval mapping with an established linkage group Li et al 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation